Clinical and epidemiological characterization of hospitalized patients with community-acquired pneumonia at the Hospital Escuela Eva Perón in the city of Granadero Baigorria, Argentina.Perón School Hospital of the city of Granadero Baigorria(Santa Fe, Argentina) years 2021-2023 - Mathurin, Esteban Pablo; Martínez Amezaga, Dr. Luis Ignacio; Operto, María Alejandra (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Community-acquired pneumonia (CAP) is a pathology of extensive prevalence in the population under study, with high morbimortality and high cost for the health system. Objectives: To describe the clinical and epidemiological characteristics of patients hospitalized for CAP at the Hospital Escuela Eva Perón in the city of Granadero Baigorria (Santa Fe, Argentina) during the period June 2021 to June 2023. Materials and methods: A quantitative, observational, descriptive, cross-sectional, retrospective study was carried out. A population of 91 male and female patients over 18 years of age admitted with a diagnosis of CAP in the medical clinic area of the Hospital Escuela Eva Perón was studied. The epicrises of the patients included in the study were observed and data from the history, physical examination and complementary studies were collected, which led to the creation of a data table for subsequent statistical analysis. Results: During the period studied, 91 patients were admitted with CAP, which constituted 5% of all admissions. The mean age was (52.0 ±16.9) years with a male frequency of 62%. The majority risk group according to the CURB-65 scale was group 2. Arterial hypertension (AHT) was an associated comorbidity in 38.5% of patients and the average number of days of hospitalization was (7 ± 5) days. The positivity of microbiological blood culture results was 18% at the expense of Streptococcus pneumoniae. Pleural effusion was present in 28% of patients. Conclusions: The frequency of admissions for CAP in the present study is considerable in relation to total admissions. More than one third of the patients admitted were hypertensive. Most cultures were negative and among the positive cultures the most frequent microorganism was Streptococcus pneumoniae